Highly ordered TiO2 nano-pore arrays fabricated from a novel polymethylmethacrylate/polydimethylsiloxane soft template - Zhong, P.; Que, W. X. (Nano-Micro Letters, 2010)
A novel soft polymer template containing a double-layer structure, which includes a thin layer of polymethylmethacrylate (PMMA) used as a pattern layer and a thicker layer of polydimethylsiloxane (PDMS) used as a back layer, was fabricated from a replica molding process. Anodic aluminum oxide (AAO) template was used as the replica mold to be replicated to the polymethylmethacrylate layer by a thermal infiltration process under a vacuum condition. Results indicate that PMMA/PDMS soft templates with different sizes could be easily fabricated from the as-prepared AAO replica mold. The PMMA/PDMS soft templates were then employed to imprint a TiO2 gel for achieving TiO2 nano-pore arrays. After the imprinting process, the PDMS layer was firstly peeled off and the PMMA layer was then removed into acetonitrile, which can avoid any demolding problems like damages or distortions. The TiO2 nano-pore arrays with the crystalline of anatase could be obtained at a heat treatment temperature of 450°C.